Pengaruh Customer Review dan Customer Rating Terhadap Keputusan Pembelian Konsumen pada Marketplace Shopee: Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Bengkulu - Hasim Asari; Ade Tiara Yulinda (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Purchasing decision is a process where consumers evaluate various alternative choices and choose one or more alternatives based on certain considerations. Several factors that influence the purchasing decisions of online shopping consumers are customer reviews and customer ratings. This study aims to determine the effect of customer reviews and customer ratings on consumer purchasing decisions. This type of research is quantitative research with a descriptive approach. The population of this study were all students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu, who use the Shopee marketplace. The number of research samples was 90 people. Data collection was carried out by distributing questionnaires. The data analysis technique uses multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 1.577 + 0.483 X1 + 0.360 X2. The results of the analysis show that partially customer review has a positive and significant effect on purchasing decisions (tcount = 5,350 and Sig = 0.000) and customer rating has a positive and significant effect on purchasing decisions (tcount = 3,747 and Sig = 0.000). Simultaneously, there is an influence of customer review and customer rating on purchasing decisions (Fhitung = 85,744 and Sig = 0.000). It is recommended for online traders in the Shopee marketplace to be able to increase consumer purchasing decisions by increasing consumer confidence through increasing positive customer reviews and customer ratings.